EVALUASI USABILITY SISTEM UJIAN ONLINE PENERIMAAN MAHASISWA BARU INSTITUT TEKNOLOGI DAN BISNIS BANK RAKYAT INDONESIA (BRI INSTITUTE) - Rizki Adha; Sudianto, Sudianto (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2019)
The design of information must be done by taking into account the user convenience factor (usability). Usability is a very important factor and must be considered so that users who implement the information system need to be easy to use, obtain the necessary information, and are interested in entering more into the information system. This research was conducted to analyze the acceptance system of the BRI Institute acceptability of new students based on usability criteria. This study uses the System Usability Scale (SUS) method to measure the use of this online examination system for use. This SUS method has 10 questions that will be answered by the respondents involved and uses the direct system of the new student's Online Acceptance Exam. The average score obtained by the System Use Scale method is 74.67. These results fall into the Acceptable category so that the BRI Institute admissions system exam is suitable for use